2022
DOI: 10.1001/jamanetworkopen.2022.8873
|View full text |Cite
|
Sign up to set email alerts
|

Association of Influenza Vaccination With Cardiovascular Risk

Abstract: Key Points Question Is seasonal influenza vaccination associated with lower rates of adverse cardiovascular events? Findings In this meta-analysis of 6 randomized clinical trials including 9001 adults who were randomized to influenza vaccination vs matching placebo or standard care, 3.6% of vaccinated patients developed a major adverse cardiovascular event within 12 months compared with 5.4% of those who received placebo or control, a 1.8% significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…Following the IAMI trial (but before IVVE was presented), another meta-analysis was recently conducted in 2022, which included 6 RCTs including IAMI with a total of 9001 patients, 53% of whom had prior CVD [ 58 •]. Influenza vaccination reduced the composite CV outcome by 34% (HR 0.66 (0.53–0.83)), with a greater benefit seen among patients with recent ACS who experienced a 45% reduction in CV outcomes with influenza vaccination.…”
Section: Updated Meta-analysismentioning
confidence: 99%
“…Following the IAMI trial (but before IVVE was presented), another meta-analysis was recently conducted in 2022, which included 6 RCTs including IAMI with a total of 9001 patients, 53% of whom had prior CVD [ 58 •]. Influenza vaccination reduced the composite CV outcome by 34% (HR 0.66 (0.53–0.83)), with a greater benefit seen among patients with recent ACS who experienced a 45% reduction in CV outcomes with influenza vaccination.…”
Section: Updated Meta-analysismentioning
confidence: 99%
“…Cardiovascular disease is a major complication of diabetes and a serious complication of influenza [ 33 , 34 ]. A recent meta-analysis demonstrated that influenza vaccination could reduce 34% risk of major cardiovascular events [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized trial, which was published in 2011 and included 439 patients admitted to acute coronary syndromes (ACS) within 8 weeks, also found that the influenza vaccine reduced the number of major cardiovascular events in patients with ACS after a 1-year follow-up (unadjusted HR = 0.70, 95% CI: 0.57–0.86, P = 0.004) ( 23 ). A meta-analysis based on six randomized controlled studies published in 2022 also found that the influenza vaccine was associated with reduced cardiovascular risk ( 24 ), and two meta-analyses also published in 2022 further suggested that the influenza vaccine was associated with reduced cardiovascular risk in patients with heart failure ( 25 ) or coronary artery disease ( 26 ). This review shows an expanded effect of influenza vaccination on the risk of arrhythmias.…”
Section: Discussionmentioning
confidence: 99%